Application of home-based exercise therapy in community-dwelling elderly patients with mild cognitive impairment and depression (以家庭为基础的运动疗法在社区老年轻度认知障碍伴抑郁患者中的应用研究) - ZHU Haiying (诸海英); PEI Hua (裴华); YUAN Hongyan (袁红艳); ZHANG Lianhua (张莲花) (Association of Integrative Nursing, 2023)
Objective To evaluate the application effect of home-based exercise therapy in community-dwelling elderly patients with mild cognitive impairment (MCI) and depression. Methods From January 2021 to December 2022, 60 community-dwelling elderly patients with MCI and depression who were screened at medical institutions were randomly divided into the control group and the intervention group. According to the basic requirements of national public health service, community medical staff carried out group follow-up once every quarter, and patients were intervened by general lifestyle interventions and health education for 6 months. On the basis of routine interventions, the intervention group received home-based exercise therapy for 6 months. The Geriatric Depression Scale(GDS), The Montreal Cognitive Assessment (MoCA), Brathel Index (BI) for Activity of Daily Living were adopted for effectiveness assessment of exercise therapy on cognitive function, depression level and daily living ability of patients. Results After 6 months of intervention, the score ofGDS in the intervention group was lower than that in the control group, with a significant difference (P＜0. 01); The total score of MoCA and subscale scores of Visuospatial/Executive, Attention, Language, Abstraction, Delayed recall and Orientation in the intervention group were higher than those in the control group (P＜0. 01); The score of BI in the intervention group was higher than that in the control group, with a significant difference (P＜0. 01). Conclusion Home-based exercise therapy can alleviate the depressive symptoms, improve the cognitive function and activity of daily living among community-dwelling elderly patients with MCI and depression (目的 探讨以家庭为基础的运动疗法对社区老年轻度认知障碍(MCI)伴抑郁患者的影响。方法 选取2021年1月-2022年12月, 经医疗机构筛查并居住在上海市奉贤区社区的60名MCI伴抑郁症状的患者, 随机分为对照组和干预组。对照组依据国家基本公共卫生服务要求, 由课题组成员在相应社区每季度开展团体讲座, 普及MCI相关健康教育知识, 饮食、运动等生活方式, 干预6个月; 干预组在对照组的基础上, 增加了以家庭为基础的运动疗法, 干预6个月。对比两组患者老年抑郁量表(GDS)、蒙特利尔认知评估量表(MoCA)和Barthel指数评定量表(BI)得分情况。结果 干预后, 干预组GDS量表评分低于对照组, 差异有统计学意义(P＜0. 01); 干预组MoCA量表视空间与执行能力、注意力、语言功能、抽象思维、延迟回忆和定向力维度评分以及总分高于对照组, 差异有统计学意义(P＜0. 01); 干预组患者BI量表评分较对照组提高, 差异有统计学意义(P＜0. 01)。结论 以家庭为基础的运动疗法可以缓解社区老年MCI伴抑郁患者的抑郁症状, 改善认知功能, 提高日常生活能力, 并延缓MCI病情进展。)